Evaluation of Hematological Parameters in Partial Exchange and Packed Cell Transfusion in Treatment of Severe Anemia in Pregnancy - Sudha Salhan; Vrijesh Tripathi; Rajvir Singh; Harsha S. Gaikwad (Anemia)
Objectives. Anemia is a major public health problem throughout the world which assumes prominence in pregnant mothers. Patients with severe anemia continue to present themselves at term or in labor. This study was conducted to compare the improvements in hematological parameters of patients receiving partial exchange blood transfusion and transfusion of packed cells without exchange. Methods. One hundred and twenty-five severely anemic antenatal mothers were admitted from outpatient service. Partial exchange transfusion was given to sixty-six patients while fifty-nine received transfusion of packed cells with frusemide cover. Results. The two groups were comparable in terms of age, height, weight, religion, diet, education, occupation of self and husband, and income. Hemoglobin level in Group 1 was comparatively less than Group 2 at prelevel (5.2±1.5 versus 6.6±2.3, P=0.001) and postlevel (7.2±1.5 versus 8.6±1.8, P=0.001), respectively, but there was no significant difference between the two modes of transfusion (2.09±1.6 versus 2.01±1.5, P=0.78). Conclusion. The study produced an equally significant improvement in hematological parameters in partial exchange and packed cell transfusion. Platelet counts were significantly less in partial exchange as compared with packed cell transfusion.